Venous Thromboembolism at Low Risk of Recurrence in Young Women: Stress and Violence Associated with Recurrence. An International Case-Control Study - Bitsadze, Victoria; Nikolaeva, Mariya Gennadevna; Mousty, Ève; Khizroeva, Jamilya; Laurent, Jérémy; Ripart, Sylvie; Kudryavtseva, Ekaterina; Collen, Lorris Le; Shatilina, Anastasia; Allal, Salim; Lyadnova, Elizaveta; Fortier, Mathieu; Bouvier, Sylvie; Chea, Mathias; Zainulina, Marina Sabirovna; Perez-Martin, Antonia; Makatsariya, Alexander; Gris, Jean-Christophe (Thrombosis and Haemostasis, 2024)
Background In young women with venous thromboembolism (VTE) related to weak transient risk factors, it remains unknown whether stress levels and intimate partner violence (IPV) are associated with recurrence. The VTE-WEAK study aims to investigate the association between perceived stress and IPV with a recurrence of VTE in women with a first episode of VTE due to combined oral contraceptives, pregnancy-puerperium, minor trauma/fracture, brief surgery, infection or brief immobility, and not using antithrombotic prophylaxis.Material and Methods We performed a multicenter, international, observational, retrospective study on women referred for thrombophilia screening who were subsequently monitored. Patients were aged 18 to 55 years old and free of high-risk thrombophilia. When a recurrence of VTE was suspected for the first time, the perceived stress level and IPV were evaluated using self-administrated PSS-10 and Woman Abuse Screening Tool (WAST) questionnaires.Results We monitored 7,754 women over 43,880 patients–years. A first suspected recurrence occurred in 4,772 women, among whom 1,316 had an objectively confirmed recurrence. The perceived stress level and an IPV situation were both independent risk factors for recurrence: moderate stress: adjusted odds ratio (aOR) 1.630 (1.415–2.468); high perceived stress: aOR 10.03 (7.528–13.36); IPV: 1.953 (1.546–2.468), p < 0.0001.Conclusion The perceived level of stress and IPV are associated with a recurrence of VTE when suspected. The mechanisms and clinical consequences of a possible stress coagulopathy require investigation.
Keywords: venous thromboembolism; recurrence; risk factor; stress; intimate partner violence